Bilateral Type-I Duane's Retraction Syndrome with bilateral Crocodile Tears: A Case Report - Pagad, Harsha; Ramnani, Pooja; Karandikar, Sumita; Tadwalkar, Archana; Shanbhag, Nita; Nair, Akshay G (Nepalese Journal of Ophthalmology, 2018)
Background: Duane's retraction Syndrome is a congenital form of strabismus characterized by horizontal eye movement limitation and globe retraction with palpebral fissure narrowing in attempted adduction. It may be associated with co-existing ocular and systemic pathologies. Crocodile tears, or a paradoxical gustatory lacrimal reflex can be either congenital or acquired. The congenital cases typically are associated with Duane’s syndrome in most of the cases.Case: We present in our case report, uncommon case of bilateral Duane’s syndrome with bilateral crocodile tears - both of which can be assumed to be of probably central origin. Though several cases have been reported, there are very few from the Indian subcontinent. Here, we also review the literature of the syndrome with crocodile tears.Conclusion: All cases of Duane’s retraction syndrome warrant a thorough screening for coexisting ocular and systemic abnormalities. Ours is a classic report of bilateral Duane’s syndrome with bilateral congenital crocodile tears, the coexistence of these two anomalies emphasising the aetiology to be anomalous innervation occurring at central level i.e. is brain stem.